Chernets M.V. Influence of straight bevel gear teeth hooking conditions on their contact strength. - Чернець, М.В. (Problems of Tribology, 2014)
The influence of conditions of straight bevel gear teeth contact, which is connected with number of teeth pairs, that are in the gearing, on the level of maximal contact pressures has been researched. Calculation has been conducted on the basis of equivalent cylindrical gear with front, medium and internal modules of conic gear. Contact pressures reach their maximal values at the internal teeth butt end. As the result of conducted researches there has been established, that according to standardized technique of contact teeth strength calculation, pressures level would be 1,48 times higher, than according to developed technique, which allows to take into account the parity of gearing.